2014
DOI: 10.1371/journal.pone.0096840
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Neurocognitive Processes Reflected by P600 Effects: Evidence from ERPs and Neural Oscillations

Abstract: Research on language comprehension using event-related potentials (ERPs) reported distinct ERP components reliably related to the processing of semantic (N400) and syntactic information (P600). Recent ERP studies have challenged this well-defined distinction by showing P600 effects for semantic and pragmatic anomalies. So far, it is still unresolved whether the P600 reflects specific or rather common processes. The present study addresses this question by investigating ERPs in response to a syntactic and pragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
71
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 68 publications
(112 reference statements)
13
71
1
Order By: Relevance
“…Similarly, Klimesch (1996) reported semantic difficulties to alleviate upper alpha activity. Reduction of alpha activity, furthermore, could be observed in response to ironic items, concomitant with enhanced P200 and P600 deflections (Regel et al, 2014). In line with these findings, the present study found suppression of spectral MEG activity within the alpha band (and slightly higher frequencies) in case of context-mismatching PSPs.…”
Section: Alpha Powersupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, Klimesch (1996) reported semantic difficulties to alleviate upper alpha activity. Reduction of alpha activity, furthermore, could be observed in response to ironic items, concomitant with enhanced P200 and P600 deflections (Regel et al, 2014). In line with these findings, the present study found suppression of spectral MEG activity within the alpha band (and slightly higher frequencies) in case of context-mismatching PSPs.…”
Section: Alpha Powersupporting
confidence: 90%
“…Such inhibitory operations might help to avoid premature lexical access and semantic assignments that are facilitated by the context, but do not match the actual text of the test sentences. An enhanced P200 deflection -followed by a P600 -has also been documented for the processing of irony (Regel, Meyer, & Gunter, 2014). In case of irony, immediate access to the ''correct'' lexical meaning leads to incorrect interpretations and, therefore, has to be inhibited in order to provide the temporal resources for additional operations, e.g., negation.…”
Section: Amplitude Of M200cmentioning
confidence: 98%
“…For example, the comprehension of ironic versus literal meanings has revealed an increase in this P600 ERP component (Regel, Coulson, & Gunter, 2010;Regel, Gunter, & Friederici, 2011;Regel, Meyer, & Gunter, 2014). To date, the P600 functional interpretation remains controversial.…”
mentioning
confidence: 99%
“…Originally obtained for syntactic violations and ambiguities, it is also observed following semantic abnormalities (see Kuperberg, 2007, for a review). A recent study distinguishes between a widespread P600 reflecting reanalysis or repair processes that follow syntactic anomalies and a more constrained centro-parietal P600 to pragmatic anomalies, such as the processing of ironic messages (Regel et al, 2014). However, a P600 effect most prominent over frontal electrode sites has also been reported for the processing of ironic versus literal statements (Spotorno, Cheylus, Van Der Henst, & Noveck, 2013).…”
mentioning
confidence: 99%
“…Here, three remarks are in order. First, recent research suggests that different instances of what appears to be a P600 might reflect different underlying brain processes (Regel et al, 2014;DeLong et al, 2014). Therefore, some prudence is advised when comparing P600 effects across experiments and paradigms.…”
Section: Introductionmentioning
confidence: 99%